Impact of Double Taxation Avoidance Agreements on Foreign Direct Investment in Nepal (Economic Journal of Nepal, 2020)
Developing countries like Nepal enter the Double Taxation Avoidance (DTA) Treaties agreements to increase inflow of Foreign Direct Investment. Since DTA avoid simultaneous tax payments by a taxpayer for same income or assets in multiple jurisdictions and be instrumental in promoting cross-border investments and capital transfer among DTA signing countries. However, empirical studies have shown mixed results. This study attempts to assess the impact of Double Taxation Avoidance (DTA) Treaties on inflow of Foreign Direct Investments (FDIs) in Nepal. This study uses a comprehensive panel database containing annual flow of FDI from 89 countries for the period of 1990-2016 as well as other factors that might affect FDI flow into the country. We used pooled OLS and fixed effect methods. The study finds that singing DTA agreement have had small but positive impact on the inflow of FDI. Specifically, Nepal receives, on average, between 91.90 to 216.54 million more FDI per country per year from countries with DTA agreement compared to countries without such agreement.